Optimization of Kendari Police Satlantas Dikmas Activities for Students in Improving Kamseltibcar - Larwanda Agung Maulana (Indonesian Journal of Police Studies, 2021)
The phenomenon of traffic violations that is increasingly happening today makes it impossible to create a safe and orderly community life, especially in this case the students who are the object of the traffic violation. Supervision carried out by parents and teachers at school is still not sufficient in handling students so they do not commit traffic violations. The most effective way is with the Traffic Dikmas activities scheduled by the Kendari Police Satlantas. But even though these activities have been carried out, they still have not been able to reduce the number of traffic violations committed by students. The concepts and theories used are POAC management theory, communication theory, and motivation theory. The results of the study found that the Kendari Police District Education and Community Service activities after being analyzed using the POAC management theory had been running for 2 months and were judged as the program implemented not optimally because there were still shortcomings in each stage of the activity and there were benefits from the side of knowledge about past community education activities, how the method was used. used in education, and reducing the number of traffic violations by students. While the inhibiting factors are environmental factors, behavioral factors, and also the influence of students' thinking which is less aware of traffic rules. In this study, the factors that support and hinder the optimization of the Kendari Police Satlantas activities for students to improve Kamseltibcar, namely from human resources, budget, methods, materials, machines, and markets as inputs to improve the performance of members of the later dikyasa unit in Kendari Police and Police. Some of the points conveyed by the author in this thesis aim to provide suggestions to improve the performance of the Kendari Police Satlantas in the future. Based on the results of the study, the authors suggest that members of the Dikyasa Unit at the Kendari Police in optimizing direct social education activities for students in order to improve kamseltibcar must make improvements in the HR sector, provide training and schools for direct members of the Dikyasa unit so that they can carry out direct social activities for students. by utilizing technology and adapting to the times, not with monotonous methods. The suggestion put forward by the next researcher is to analyze how students know about traffic rules.